International handbook on shareholders' agreements regulation, practice and comparative analysis - Mock, Sebastian; Csach, Kristian; Havel, Bohumil, 1975- (Walter de Gruyter GmbH, 2018)
Shareholders´ Agreements have a growing influence on the general understanding of corporate law since they bind not only the shareholders but also affect the constitution of the corporation and can have a severe impact on capital markets. Therefore, Shareholders´ Agreements are more and more subject to regulation in corporate, capital market and also insolvency law on the national, the European and the international level. This handbook provides a general examination of conceptual questions of Shareholders´ Agreements and provides an analysis of the regulation of Shareholders´ Agreements in European and international law and of the national law of more than 20 jurisdictions. Readers will get a general understanding of the theoretical and practical problems involved with Shareholders´ Agreements and detailed information on the regulation of Shareholders´ Agreements in several jurisdictions and the applicable law in the case of transnational corporations and cross-border transactions.